2014
DOI: 10.1016/j.celrep.2014.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of NCOA6 Leads to Dilated Cardiomyopathy

Abstract: Summary Dilated cardiomyopathy (DCM) is a progressive heart disease characterized by left ventricular dilation and contractile dysfunction. Although many candidate genes have been identified using mouse models, few of them have been shown to be associated with DCM in humans. Germline depletion of Ncoa6, a nuclear hormone receptor coactivator, leads to embryonic lethality including heart defects. However, it is unclear whether Ncoa6 mutations cause heart diseases in adults. Here, we report that two independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…For example, it has been suggested that mutations in genes encoding contractile proteins result in functional changes and lead to contractile dysfunction of cardiomyocytes ( 34 , 35 ). The majority of patients with DCM exhibit autosomal dominant genetic disease, although there are several reported cases with recessive, X-linked, and other patterns of inheritance ( 11 , 12 , 14 , 15 ). Thus, the Heart Rhythm Society/European Heart Rhythm Association expert consensus statement recommends the performance of genetic testing on patients with DCM.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been suggested that mutations in genes encoding contractile proteins result in functional changes and lead to contractile dysfunction of cardiomyocytes ( 34 , 35 ). The majority of patients with DCM exhibit autosomal dominant genetic disease, although there are several reported cases with recessive, X-linked, and other patterns of inheritance ( 11 , 12 , 14 , 15 ). Thus, the Heart Rhythm Society/European Heart Rhythm Association expert consensus statement recommends the performance of genetic testing on patients with DCM.…”
Section: Discussionmentioning
confidence: 99%
“…However, following a thorough review of secondary causes, a substantial portion of DCM cases remain unexplained and such DCM is defined as idiopathic DCM, among which 25-50% of DCM cases occur in at least two closely related family members, hence termed familial DCM (10). Aggregating evidence has demonstrated that genetic defects play a crucial role in the development of DCM, and mutations in >60 genes have been associated with DCM (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Among the DCM-associated genes, the majority encode sarcomeric, Z-disc and cytoskeletal proteines that are responsible for the generation and transmission of contractile force, and are inherited predominantly in an autosomal dominant mode, with the autosomal recessive, X-linked, or mitochondrial mode of inheritance less frequent (10).…”
Section: Introductionmentioning
confidence: 99%
“…In co-expression networks, the top genes are the most connected genes, based on the correlation structure. We identified a number of hub genes that may function as molecular drivers of cardiac remodeling: Gsk3a (Ribo2), characterized for its role in regulating glycogen metabolism, and shown to be a critical player in cardiac hypertrophy (Sugden et al, 2008;Zhou et al, 2016); Cand2 (Ribo2), a mTOR dependent mRNA recently identified as a growth regulator, upregulated in the acute phase of cardiac hypertrophy (Sandmann et al, 2018); Vldlr (RNA2), characterized for its role in obesity associated lipotoxicity (Fungwe et al, 2019), and negatively associated with survival in the ischemic heart (Perman et al, 2011); Eif3d (Ribo14), thought to be involved in cap-dependent translation during cellular stress, independently of Eif4e (Lee et al, 2016); Immt (Ribo15), a mitochondrial membrane protein whose transcript is regulated by Rbm20 (Zahr and Jaalouk, 2018); Ncoa6 (RNA16), whose dysfunction is linked to dilated cardiomyopathy in mouse models (Roh et al, 2014); Slc25a3 (RNA14), the absence of which was shown to drive a novel model of metabolic, mitochondrial-driven cardiomyopathy (Kwong et al, 2014); or Zmpste24 (RNA17), which may be implicated in prelamin A toxicity-driven inflammation (Brayson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%